Leveraging the Medicines for Malaria Venture malaria and pathogen boxes to discover chemical inhibitors of East Coast fever - Nyagwange, James; Awino, Elias; Tijhaar, Edwin; Svitek, Nicholas; Pelle, Roger; Nene, Vishvanath M. (Elsevier, 2019)
Chemotherapy of East Coast fever, a lymphoproliferative cancer-like disease of cattle causing significant economic losses in Africa, is largely dependent on the use of buparvaquone, a drug that was developed in the late 1980's. The disease is caused by the tick-borne protozoan pathogen Theileria parva. Buparvaquone can be used prophylactically and it is also active against tropical theileriosis, caused by the related parasite Theileria annulata. Recently, drug resistance was reported in T. annulata, and could occur in T. parva. Using a 3H-thymidine incorporation assay we screened 796 open source compounds from the Medicines for Malaria Venture (MMV) to discover novel chemicals with potential inhibitory activity to T. parva. We identified nine malaria box compounds and eight pathogen box compounds that inhibited the proliferation of F100TpM, a T. parva infected lymphocyte cell line. However, only two compounds, MMV008212 and MMV688372 represent promising leads with IC50 values of 0.78 and 0.61 μM, respectively, and CC50 values > 5 μM. The remaining compounds exhibited a high degree of toxicity (CC50 values < 1.09 μM) on the proliferation of bovine peripheral blood mononuclear cells stimulated with concanavalin A. We also tested the anti-cancer drug, dasatinib, used in the chemotherapy of some leukemias. Dasatinib was as active and safe as buparvaquone in vitro, with an IC50 of 5 and 4.2 nM, respectively, and CC50 > 10 μM. Our preliminary data suggest that it may be possible to repurpose compounds from the cancer field as well as MMV as novel anti-T. parva molecules.